Okoljska estetika Sarajeva - Husukić, Erna (Urbani izziv, 2017)
This article discusses aesthetic singularity in present-day Sarajevo and shows how time generates a social response to the visual quality of space. Acknowledging the metamorphosis of the cityscape with regard to the identity reformulation of post-war Sarajevo, it examines the sensory engagement of people with the urban environment in relationship to the traumatic events and shifting realities imposed by globalisation. The hypothesis is that the environmental aesthetics of post-war cities are defined by the traumatic memory of physical and social destruction. This article offers insight within a broad range of theoretical discussions on the changes in the visual language and aesthetic quality of urban spaces in post-war Sarajevo. In particular, it presents the notion of urban memory and its role in shaping the aesthetic experience in postwar cities. Finally, the findings show that architectural remnants, or ruins in the urban fabric, instead of being unstable entities, have the potential to become drivers of a continuum. Ultimately, this article accepts the values of incompleteness and opens new perspectives towards playful experimentation, which potentially relieves the aesthetic experience of a rigid and monotonous urban image.
Keywords: identiteta; mesta; Sarajevo; urbani prostor; urbanistični razvoj